Pretransplant human leukocyte antigen antibodies detected by single-antigen bead assay are a risk factor for long-term kidney graft loss even in the absence of donor-specific antibodies - Richter, Rudolf; Süsal, Caner (Transplant international, 2016)
Clinical relevance of ELISA- and single-antigen bead assay (SAB)-detected pretransplant HLA antibodies (SAB-HLA-Ab) for kidney graft survival was evaluated retrospectively in 197 patients transplanted between 2002 and 2009 at the University Clinic Frankfurt. Having adjusted for retransplantation and delayed graft function, a significantly increased risk for death-censored graft loss was found in patients with pretransplant SAB-HLA-Ab [HR: 4.46; 95% confidence interval (CI): 1.47-13.48; P = 0.008]. The risk for increased graft loss was also significant in patients with pretransplant SAB-HLA-Ab but without SAB-detected donor-specific Ab (SAB-DSA) (HR: 4.91; 95% CI of 1.43-16.991; P = 0.012). ELISA was not sufficient to identify pretransplant immunized patients with an increased risk for graft loss. In immunized patients, graft loss was predominantly present in patients who received transplants with a mismatch on the HLA-DR locus. In conclusion, even if our study is limited due to small sample size, the results show an increased risk for long-term graft loss in patients with pretransplant SAB-HLA, even in the absence of DSA. SAB-HLA-Ab-positive patients, being negative in ELISA or CDC assay, might profit from a well-HLA-DR-matched graft and intensified immunosuppression.
Gesehen am 21.10.2021